Superlattice copper selenide composite material based on small organic molecules as well as preparation and application of superlattice copper selenide composite material
By using superlattice copper selenide composite materials based on organic small molecules in aqueous zinc ion batteries, the problems of cyclic stability and durability of zinc ion batteries are solved, and the battery performance with high magnification capacity retention and long cycle life is achieved.
Patent Information
- Application Number
- CN202510391253.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-06-10
- Estimated Expiration
- 2045-03-31
AI Technical Summary
The cycle stability and durability of aqueous zinc ion batteries are limited by problems such as high activity of zinc metal, slow diffusion kinetics of zinc ion and high energy consumption of material preparation methods.
The superlattice copper selenide composite material based on organic small molecules is used to insert organic small molecules into the lattice of the copper selenide body phase by diethylene triamine. The composite material is prepared by radiation reduction method to form a nanosheet-like structure with zinc ions, and improve the ion diffusion kinetics and rate performance.
The excellent rate performance and long cycle life of the negative electrode material of the aqueous zinc ion battery are achieved, which reduces the energy consumption and process complexity of material preparation, and improves the durability and robustness of the battery.
Smart Images

Figure CN120127135A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical fields of new materials and electrochemistry, and particularly relates to a superlattice copper selenide composite material based on organic small molecules, a preparation method thereof, and an application thereof. Background Art
[0002] As a new type of green electrochemical secondary energy storage device, aqueous zinc-ion batteries have become a research hotspot for replacing traditional organic lithium-ion batteries in large-scale electrical devices and wearable electronic devices due to their low cost, excellent safety, and biocompatibility. However, the corrosion, passivation, and hydrogen evolution problems of the highly active zinc metal anode in weakly acidic aqueous electrolytes seriously limit the cycle stability of the battery and reduce its durability in practical application systems. At the same time, the continuous uneven stripping / deposition of zinc ions on the anode surface easily triggers dendrite growth, resulting in short circuits and further shortening the service life of aqueous zinc-ion batteries. Although metal surface coating modification, electrolyte optimization, and electrode structure design can alleviate the occurrence of side reactions at the electrode-solution interface, they cannot fundamentally solve the problem of the high activity of zinc metal. Therefore, it is necessary to develop high-stability alternative anode materials with excellent zinc storage capacity to address the huge challenges faced by aqueous batteries. Currently, elemental and transition metal compound anodes based on chalcogen elements (S, Se, and Te) have received extensive attention due to their abundant resources, easily tunable structural compositions, and multi-electron redox energy storage mechanisms. Among them, zincophilic transition metal selenides have both metallic conductivity and high theoretical capacity, and can maintain a high Coulombic efficiency during long-cycle tests, storing zinc ions reversibly through a conversion-type reaction to the greatest extent. Compared with the structural collapse caused by the rapid insertion / extraction of zinc ions during the intercalation process, transition metal selenides can maintain the structural integrity during repeated charge-discharge cycles through solid-solid conversion reactions. However, due to the slow zinc-ion diffusion kinetics in the bulk phase of the material, the electrochemical performance of transition metal selenide anodes is generally limited by the problem of insufficient reversible capacity release at high current densities, resulting in an imbalance in the usage ratio of the positive and negative electrode materials of aqueous zinc-ion batteries and a low overall power density. Therefore, developing new high-energy transition metal compound anode materials and reducing the zinc-ion diffusion barrier through crystal structure optimization and design to improve the rate performance are the keys to realizing high-power density practical zinc-ion batteries.
[0003] Li et al. (J. Li., ACS Nano 2023, 17, 18507-18516.) prepared a non-stoichiometric cubic copper selenide material by chemical precipitation method, and confirmed its great potential as a metal-free anode for aqueous zinc-ion batteries. The cubic copper selenide material can exhibit excellent zinc storage behavior under high areal loading conditions and still has 3.1 mAh cm after continuous operation for 4100 hours. -2High reversible capacity. However, the zinc ion migration rate of the bulk copper selenide material without morphology regulation and crystal structure modification is still too low, and the rate capacity retention rate cannot be adapted to the cathode material. Li Qingwen et al. (CN118026152A) synthesized a one-dimensional carbon-coated copper selenide nanowire coaxial heterostructure material by chemical vapor deposition method. Through the one-dimensional structure design, the specific surface area of the material was increased and the ion diffusion path was effectively shortened. The external carbon layer and the heterostructure synergistically improved the electron transport rate on the electrode surface, thus improving the rate performance and stability of copper selenide. However, the high-temperature and overly complex material synthesis steps are not conducive to the green batch preparation of electrodes in the actual system. Cui Fuhan et al. (CN117855469A) prepared a new type of highly active nanoscale ruthenium selenide anode material, which can be compatible with a wide pH electrolyte system from alkaline to acidic. The aqueous zinc ion full battery assembled with ruthenium selenide and manganese dioxide exhibits a reversible capacity of 147 mAh g -1 and can operate stably for 100 cycles. However, due to the relatively heavy atomic mass of ruthenium atoms, the theoretical specific capacity it possesses is not sufficient to achieve sufficient zinc storage behavior at high current densities. At the same time, under the limitation of the relatively high zinc ion diffusion barrier, frequent charge and discharge behaviors will cause the fragmentation and pulverization of the electrode, resulting in a rapid decay of the reversible capacity and a poor cycle stability. Summary of the Invention
[0004] The object of the present invention is to develop a transition metal selenide composite material with excellent rate performance, long cycle service life and low cost, so as to solve the problems existing in the current metal-free anodes, such as low reversible capacity, slow zinc ion diffusion kinetics, poor structural stability, high energy consumption and cumbersome preparation methods.
[0005] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] In the first aspect of the present invention, a superlattice-structured copper selenide composite material based on organic small molecules is provided, in which the organic small molecules are inserted into the bulk lattice of copper selenide to form a superlattice structure. Among them, the molecular formula of copper selenide is Cu 2-x Se, 0.01 ≤ x ≤ 0.4; the organic small molecules are aliphatic amine organic small molecules, and the mass content of the organic small molecules in the composite material is 0.1% - 10%.
[0007] In the superlattice-structured copper selenide composite material based on organic small molecules of the present invention, the superlattice intercalation realized by the organic small molecules effectively modulates the electronic structure of cubic copper selenide and increases the charge density of Cu and Se sites.
[0008] In the present invention, when the organic small molecule is diethylenetriamine (DETA), the composite material is denoted as Cu 2- xSe-DETA。
[0009] Preferably, the organic small molecule-based superlattice copper selenide composite material of the present invention has a two-dimensional nanosheet structure. In some embodiments of the present invention, the composite material is assembled into a flower-like microsphere morphology with two-dimensional nanosheets having a thickness of 2-5 nm.
[0010] Furthermore, in the above-mentioned organic small molecule-based superlattice copper selenide composite material, it is preferred that 0.05 ≤ x ≤ 0.3.
[0011] Furthermore, the above-mentioned organic small molecule-based superlattice copper selenide composite material is prepared by a one-step radiation reduction method. Under the regulation of organic small molecules, the selenosulfite and copper ions in the precursor solution are reduced by the hydrated electrons generated by water radiolysis, and the two combine to obtain the organic small molecule-based superlattice copper selenide composite material.
[0012] In the second aspect of the present invention, there is provided a method for preparing the above-mentioned organic small molecule-based superlattice copper selenide composite material, comprising the following steps:
[0013] 1) First, prepare an aqueous solution of a copper precursor and add a certain volume of an organic small molecule solvent thereto;
[0014] 2) Add a certain amount of selenosulfite solution to the above-mentioned mixed solution, after adding a radical scavenger, introduce an inert gas and seal it, and carry out a radiation reduction reaction using γ-rays or an electron beam;
[0015] 3) Filter, wash, and vacuum dry the solid obtained from the radiation reduction reaction to obtain the organic small molecule-based superlattice copper selenide composite material.
[0016] In the above step 1), the copper precursor is a copper salt, which can be selected from one or more of copper nitrate, copper sulfate, copper chloride, and copper acetate.
[0017] In the above step 1), the organic small molecule is selected from one or more of aliphatic amine small molecules having multiple amine sites such as diethylenetriamine, ethylenediamine, triethylenetetramine, tetraethylenepentamine, and ethylenediaminetetraacetic acid.
[0018] In the above step 2), the radical scavenger is an alcohol organic solvent, which can be selected from one or more of n-propanol, isopropanol, tert-butanol, ethylene glycol, and glycerol.
[0019] In the above step 2), the inert gas can be nitrogen, argon, or a mixed gas thereof, and the gas introduction time is 1-30 min.
[0020] In the above step 2), if γ-ray irradiation is selected, the sample is placed in an irradiation tube and sealed with an inert gas, and used with60 The γ-rays generated by Co are used for radiation reduction reaction. Preferably, γ-ray irradiation is carried out at room temperature, the dose rate is 50-400 Gy / min, and the absorbed dose is 20-400 kGy.
[0021] In the above step 2), if electron beam irradiation is selected, the sample is injected into a plastic bag and sealed with an inert gas, and the radiation reduction reaction is carried out using an electron accelerator irradiation device at room temperature. The energy of the electron accelerator is preferably 0.1-20 MeV, the dose rate of electron beam irradiation is 2-50 kGy / pass, and the absorbed dose is 50-500 kGy.
[0022] In some embodiments of the present invention, the concentration of copper ions in the irradiated sample is 2-100 mmol / L, preferably 4-50 mmol / L, and more preferably 8-40 mmol / L.
[0023] In some embodiments of the present invention, the organic small molecule is diethylenetriamine, and its addition amount in 28 mL of the irradiated sample is 0.2-15 mL, preferably 0.4-10 mL, and more preferably 0.6-5 mL.
[0024] In some embodiments of the present invention, the concentration of sodium selenosulfate solution in the irradiated sample is 2-200 mmol / L, preferably 5-100 mmol / L, and more preferably 10-50 mmol / L.
[0025] In some embodiments of the present invention, the concentration of the radical scavenger in the irradiated sample is 10-500 mL / L, preferably 50-400 mL / L, and more preferably 100-300 mL / L.
[0026] In the third aspect of the present invention, there is provided an application of the above-mentioned organic small molecule-based superlattice copper selenide composite material as an electrode material in an aqueous zinc ion battery, and the aqueous zinc ion battery can be a button battery, a flexible soft-pack battery, a flexible fibrous battery, a non-flexible soft-pack battery, etc.
[0027] In some embodiments of the present invention, there is provided a button battery device, and the button battery device includes the electrode material such as Cu 2-x Se-DETA as described above. It should be noted that for the button battery device provided by the present invention, except that the electrode material uses the electrode material provided by the present invention, the other components required for forming the button battery device, such as current collector, battery case, spring piece, gasket, electrolyte, zinc foil, separator, etc., can all adopt the relevant technical solutions in the prior art, and the present invention does not limit them here.
[0028] In some embodiments of the present invention, a flexible pouch battery device is provided, and the flexible pouch battery device includes the electrode material such as Cu as described above 2-x Se-DETA. It should be noted that for the flexible pouch full battery device provided by the present invention, except that the electrode material adopts the electrode material provided by the present invention, other components required to form the flexible pouch full battery device, such as a plastic sealing machine, graphite foil, manganese dioxide, gel electrolyte, separator, etc., can all adopt the relevant technical solutions in the prior art, and the present invention does not limit them here.
[0029] The present invention also provides an electric device product, and the electric device product includes a battery device such as the flexible pouch battery as described above. It should be noted that other parts of the device product except the aforementioned device can adopt the relevant technical solutions in the prior art, and the present invention does not limit them here. The electric device product is preferably a flexible display screen, a fan, a mobile phone, etc.
[0030] Compared with the prior art, the present invention has the following technical advantages:
[0031] (1) In the present invention, organic small molecules such as diethylenetriamine are used as morphology regulation and superlattice intercalation organic molecules, and a superlattice copper selenide composite based on organic small molecules is synthesized by a radiation reduction method. The composite material has a zinc ion-accessible nano-sheet structure, which increases the contact area with the electrolyte, thereby promoting the improvement of the reversible capacity. At the same time, organic small molecules such as DETA are inserted into the bulk lattice of copper selenide to form a superlattice structure, weakening the migration barrier of zinc ions and improving the ion diffusion kinetics, effectively improving the rate performance and structural stability of the material. Due to the charge repulsion induced by the electron transfer of DETA molecules from the N atom to the Cu and Se sites, lattice stress is induced, further regulating the electrochemical properties of copper selenide. Therefore, Cu 2-x Se-DETA has excellent conductivity and reversible zinc storage ability, and can exhibit a high rate capacity retention rate at a high current density.
[0032] (2) The superlattice copper selenide based on organic small molecules synthesized in the present invention has excellent rate performance and cycle stability as the negative electrode material of the aqueous zinc ion battery. The assembled flexible pouch full battery can withstand a wide operating temperature from -20 °C to 40 °C, and can stably operate under the bending conditions of 0° - 180°, having excellent durability and robustness.
[0033] (3) Compared with the inorganic nanoparticle synthesis strategies such as conventional hydrothermal method, electrodeposition method and microwave-assisted method, the synthesis of organic small molecule superlattice copper selenide composites by ionizing radiation method is green, mild, flexible and controllable, with low energy consumption and little environmental pollution, which is conducive to the design of atomic defects and weakens the damage to the structure and morphology of transition metal selenides during the preparation process. Description of the Drawings
[0034] Figure 1 . Schematic diagram of the preparation process and structure of the superlattice copper selenide composite material based on diethylenetriamine molecules in the present invention.
[0035] Figure 2 . X-ray diffraction spectrum (XRD) pattern of the Cu 2-x Se-DETA composite material prepared in Example 1.
[0036] Figure 3A . Scanning electron microscope (SEM) image of the Cu 2-x Se-DETA composite material prepared in Example 1.
[0037] Figure 3B . Transmission electron microscope (TEM) image of the Cu 2-x Se-DETA composite material prepared in Example 1.
[0038] Figure 4A . X-ray photoelectron spectroscopy (XPS) pattern of the Cu 2-x Se-DETA composite material prepared in Example 1.
[0039] Figure 4B . High-resolution XPS pattern of Cu in the Cu 2-x Se-DETA composite material prepared in Example 1.
[0040] Figure 4C . High-resolution XPS pattern of Se in the Cu 2-x Se-DETA composite material prepared in Example 1.
[0041] Figure 5A . Rate performance graph of Cu 2-x Se-DETA in a water-based zinc-ion button battery.
[0042] Figure 5B . Cycling stability test graph of Cu 2-x Se-DETA in a button battery at 5 Ag -1 current density.
[0043] Figure 6A . Galvanostatic charge-discharge curves of Cu 2-x Se-DETA assembled into a flexible soft-pack battery at different temperatures.
[0044] Figure 6B .Cu 2-x Cyclic stability test diagrams of the Se-DETA assembly as a flexible pouch battery under different bending states. Detailed implementation manners
[0045] The present invention will be further elaborated in detail below through examples, but it does not limit the scope of the present invention in any way.
[0046] Example 1
[0047] Dissolve 200 mg of copper acetate in deionized water containing 3.2 mL of DETA to prepare a 12 mL aqueous solution. Then, add 2 mL of 0.25 M sodium selenosulfate solution, 8 mL of isopropanol, and 6 mL of deionized water to the above solution and mix evenly. Continuously introduce N 2 to remove the air in the system, seal it and use 60 a Co radiation source for γ-ray irradiation with a dose rate of 100 Gy / min and an absorbed dose of 100 kGy. After the irradiation reaction, filter and collect the solid, wash it 3 times with deionized water and ethanol respectively, and place it in a vacuum oven at 60 °C for 24 hours to finally obtain Cu 2-x Se-DETA, x = 0.2.
[0048] Cu 2-x The XRD, SEM, TEM diagrams and XPS diagram of the Cu Figure 2 , Figure 3A , Figure 3B and Figures 4A - 4C are shown respectively. The superlattice copper selenide prepared based on the radiation reduction method presents a cubic phase copper selenide structure, and is assembled into a flower-like microsphere morphology with a thickness of 2 - 5 nm, Figures 4A - 4C indicating that the superlattice achieved by the intercalation of DETA molecules based on the radiation method effectively modulates the electronic structure of copper selenide and improves the charge density of Cu and Se sites.
[0049] Disperse Cu 2-x Se-DETA, polyvinylidene fluoride (PVDF), and conductive carbon black in a ratio of 7:2:1 in N-methylpyrrolidone (NMP) to prepare an electrode slurry. After uniformly scraping the above slurry on the surface of a titanium foil, place it in a vacuum oven at 60 °C for 24 hours. Cut the obtained Cu 2-x Se-DETA electrode sheet into a suitable size and assemble it with a zinc foil into a button battery. Use 2 M zinc sulfate (ZnSO 4) The battery separator is a glass fiber separator. The assembled button battery is subjected to constant current charge and discharge tests on a Blue-Energy battery test system to study its rate performance and cycle stability.
[0050] Using the above method, a water-based zinc-ion button battery assembled with Cu 2-x Se-DETA as the electrode material has electrochemical performance as Figure 5A 、 Figure 5B shown. At a current density of 5 Ag -1 , Cu 2-x Se-DETA exhibits a specific capacity of 154.6 mAh g -1 , and the capacity retention rate after 10,000 cycles is 98.6%.
[0051] Taking Cu 2-x Se-DETA material as the negative electrode and manganese dioxide as the positive electrode, and assembling them with a polyacrylamide gel electrolyte containing 2 M ZnSO 4 into a flexible pouch battery to test the full-cell electrochemical activity and durability, as Figure 6A 、 6B shown. Cu 2-x Se-DETA can operate normally in a wide temperature range from -20 °C to 40 °C and maintain excellent cycle stability under different bending conditions from 0° to 180°.
[0052] Example 2
[0053] Change the dosage of diethylenetriamine in Example 1 to 0.8 mL, and other preparation conditions are the same as in Example 1. The dosage of DETA affects the degree of superlattice formation of copper selenide and thus changes its zinc storage ability in electrochemistry. Its rate performance and cycle stability assembled in the button battery are significantly reduced compared with Example 1. At a current density of 5 Ag -1 , it has a reversible specific capacity of 76.3 mAh g -1 , and the capacity retention rate after 10,000 cycles is 85.9%.
[0054] Example 3
[0055] Change the dosage of diethylenetriamine in Example 1 to 1.2 mL, and other preparation conditions are the same as in Example 1. Its rate performance and cycle stability assembled in the button battery are reduced compared with Example 1. At a current density of 5 Ag -1 , it has a reversible specific capacity of 97.5 mAh g -1 , and the capacity retention rate after 10,000 cycles is 87.5%.
[0056] Example 4
[0057] The dosage of diethylenetriamine in Example 1 was changed to 2.4 mL, and other preparation conditions were the same as those in Example 1. Its rate performance and cycle stability when assembled in a button cell were reduced compared with Example 1. At a current density of 5 Ag -1 it had a reversible specific capacity of 116.3 mAh g -1 , and the capacity retention rate after 10,000 cycles was 90.2%.
[0058] Example 5
[0059] The dosage of diethylenetriamine in Example 1 was changed to 2.8 mL, and other preparation conditions were the same as those in Example 1. Its rate performance and cycle stability when assembled in a button cell were slightly reduced compared with Example 1. At a current density of 5 Ag -1 it had a reversible specific capacity of 134.1 mAh g -1 , and the capacity retention rate after 10,000 cycles was 92.4%.
[0060] Example 6
[0061] The dose rate of radiation reduction in Example 1 was changed to 50 Gy / min, and other preparation conditions were the same as those in Example 1. The regulation of the dose rate changed the morphology and the degree of superlattice formation of the copper selenide material, thus affecting the electrochemical activity of the material. Its performance when assembled in a button cell was slightly reduced compared with Example 1. At a current density of 5 Ag -1 it had a reversible specific capacity of 126.8 mAh g -1 , and the capacity retention rate after 10,000 cycles was 93.3%.
[0062] Example 7
[0063] The dose rate of radiation reduction in Example 1 was changed to 70 Gy / min, and other preparation conditions were the same as those in Example 1. Its performance when assembled in a button cell was slightly reduced compared with Example 1. At a current density of 5 Ag -1 it had a reversible specific capacity of 131.7 mAh g -1 , and the capacity retention rate after 10,000 cycles was 94.5%.
[0064] Example 8
[0065] The dose rate of radiation reduction in Example 1 was changed to 150 Gy / min, and other preparation conditions were the same as those in Example 1. Its performance when assembled in a button cell was slightly reduced compared with Example 1. At a current density of 5 Ag -1 it had a reversible specific capacity of 122.9 mAh g -1 , and the capacity retention rate after 10,000 cycles was 92.8%.
[0066] Example 9
[0067] The dose rate of radiation reduction in Example 1 was changed to 200 Gy / min, and other preparation conditions were the same as those in Example 1. Its performance when assembled in a button battery was slightly reduced compared with that in Example 1. At a current density of 5 Ag -1 it had a reversible specific capacity of 105.5 mAh g -1 , and the capacity retention rate after 10,000 cycles was 91.3%.
[0068] Example 10
[0069] The γ-irradiation in Example 1 was changed to electron beam irradiation, with an absorbed dose of 100 kGy and a dose rate of 20 kGy / pass. Other preparation conditions were the same as those in Example 1. Its performance when assembled in a button battery was slightly reduced compared with that in Example 1. At a current density of 5 Ag -1 it had a reversible specific capacity of 145.2 mAh g -1 , and the capacity retention rate after 10,000 cycles was 95.2%.
[0070] Example 11
[0071] The absorbed dose of γ-irradiation in Example 1 was changed to 30 kGy, and other preparation conditions were the same as those in Example 1. Its performance when assembled in a button battery was slightly reduced compared with that in Example 1. At a current density of 5 Ag -1 it had a reversible specific capacity of 84.7 mAh g -1 , and the capacity retention rate after 10,000 cycles was 90.7%.
[0072] Example 12
[0073] The absorbed dose of γ-irradiation in Example 1 was changed to 70 kGy, and other preparation conditions were the same as those in Example 1. Its performance when assembled in a button battery was slightly reduced compared with that in Example 1. At a current density of 5 Ag -1 it had a reversible specific capacity of 107.3 mAh g -1 , and the capacity retention rate after 10,000 cycles was 95.9%.
[0074] Example 13
[0075] The absorbed dose of γ-irradiation in Example 1 was changed to 150 kGy, and other preparation conditions were the same as those in Example 1. Its performance when assembled in a button battery was slightly reduced compared with that in Example 1. At a current density of 5 Ag -1 it had a reversible specific capacity of 148.1 mAh g -1 , and the capacity retention rate after 10,000 cycles was 96.3%.
[0076] Example 14
[0077] In Example 1, copper chloride was selected as the copper precursor, and other preparation conditions were the same as those in Example 1. Its performance when assembled in a button battery was slightly reduced compared to Example 1. At a current density of 5 Ag -1 , it had a reversible specific capacity of 135.7 mAh g -1 , and the capacity retention rate after 10,000 cycles was 92.6%.
[0078] Example 15
[0079] In Example 1, copper sulfate was selected as the copper precursor, and other preparation conditions were the same as those in Example 1. Its performance when assembled in a button battery was slightly reduced compared to Example 1. At a current density of 5 Ag -1 , it had a reversible specific capacity of 141.8 mAh g -1 , and the capacity retention rate after 10,000 cycles was 90.9%.
[0080] Example 16
[0081] In Example 1, diethylenetriamine was replaced with ethylenediamine, and other preparation conditions were the same as those in Example 1. Its performance when assembled in a button battery was slightly reduced compared to Example 1. At a current density of 5 Ag -1 , it had a reversible specific capacity of 92.7 mAh g -1 , and the capacity retention rate after 10,000 cycles was 87.2%.
[0082] Example 17
[0083] In Example 1, diethylenetriamine was replaced with triethylenetetramine, and other preparation conditions were the same as those in Example 1. Its performance when assembled in a button battery was slightly reduced compared to Example 1. At a current density of 5 Ag -1 , it had a reversible specific capacity of 99.2 mAh g -1 , and the capacity retention rate after 10,000 cycles was 88.5%.
Claims
1. A superlattice copper selenide composite material based on organic small molecules, characterized in that: Small organic molecules are inserted into the bulk phase lattice of copper selenide to form a superlattice structure. The molecular formula of copper selenide is Cu 2-x Se, 0.01≤x≤0.4; the organic small molecule is an aliphatic amine molecule, and its mass content in the composite material is 0.1%-10%.
2. The superlattice copper selenide composite material according to claim 1, characterized in that: The composite material is a two-dimensional nanosheet structure.
3. The superlattice copper selenide composite material according to claim 2, characterized in that: The composite material is assembled into flower-like microsphere morphology with two-dimensional nanosheets with a thickness of 2-5 nm.
4. The superlattice copper selenide composite material according to claim 1, characterized in that: The organic small molecule is selected from one or more of diethylenetriamine, ethylenediamine, triethylenetetramine, tetraethylenepentamine, and ethylenediaminetetraacetic acid.
5. The superlattice copper selenide composite material according to claim 1, characterized in that: 0.05≤x≤0.3。 6. The method for preparing the superlattice copper selenide composite material based on organic small molecules according to any one of claims 1 to 5, comprising the following steps: 1) preparing a copper precursor aqueous solution and adding an organic small molecule solvent; 2) adding a sodium selenosulfite solution and a free radical scavenger to the mixed solution obtained in step 1), then introducing an inert gas and sealing the mixture, and performing a radiation reduction reaction by irradiating with gamma rays or electron beams; 3) The solid obtained by the radiation reduction reaction is filtered, washed, and vacuum dried to obtain the superlattice copper selenide composite material based on organic small molecules.
7. The preparation method according to claim 6, characterized in that: The copper precursor in step 1) is a copper salt selected from one or more of copper nitrate, copper sulfate, copper chloride, and copper acetate; the free radical scavenger in step 2) is an alcohol organic solvent selected from one or more of n-propanol, isopropanol, tert-butanol, ethylene glycol, and glycerol; step 2) uses gamma ray irradiation with a dose rate of 50 to 400 Gy / min and an absorbed dose of 20 to 400 kGy; or, electron beam irradiation is used. The dose rate is 2-50 kGy / pass, and the absorbed dose is 50-500 kGy.
8. The preparation method according to claim 6, characterized in that: In step 2), the concentration of copper ions in the sample to be irradiated is 2-100 mmol / L, and the concentration of the sodium selenosulfite solution is 2-200 mmol / L.
9. Use of the organic small molecule-based superlattice copper selenide composite material according to any one of claims 1 to 5 as an electrode material in an aqueous zinc ion battery.
10. An aqueous zinc ion battery device containing the organic small molecule-based superlattice copper selenide composite material according to any one of claims 1 to 5, including but not limited to button batteries, flexible soft-pack batteries, flexible fiber-shaped batteries, and non-flexible soft-pack batteries.
11. An electric device product comprising the aqueous zinc ion battery device according to claim 10.
Citation Information
Patent Citations
Preparation of novel aqueous zinc ion battery negative electrode material
CN117855469A
One-dimensional carbon-coated copper selenide nanowire coaxial heterogeneous material as well as preparation method and application thereof
CN118026152A
Method for synthesizing copper indium diselenide nanosheet through ion exchange method
CN102923763A
Cu2-xSe nanomaterial used as lithium ion battery electrode material, and preparation method thereof
CN108933257A
Preparation method of nano tricopper diselenide
CN1443706A